(untitled) - Marlow, Louise (New York, NY, 1997)
By analyzing a wide range of Arab and Persian literature, Louise Marlow demonstrates that Islam's initial orientation was markedly egalitarian, but the social aspect of this egalitarianism was soon undermined in the aftermath of Islam's political success. Although the memory of its early promise never entirely receded, social egalitarianism was soon associated with political subversion. The originality and chronological scope of Louise Marlow's book will ensure a wide readership of Islamic historians and of scholars assessing the impact of the recent Islamic revival
Keywords: Equality,Equality,Social justice,Bình đẳng xã hội,Công bằng xã hội,Công bằng xã hội; Islamic countries,History,Religious aspects,Islam,History,Lịch sử; Islamic countries,Các quốc gia Hồi giáo,Các quốc gia Hồi giáo